Hubungan Lima Dimensi Teamworks dengan Kinerja Pemberian Tablet Fe3 - Nafiah, Nilam Cahya; Maulida, Vetty Silvana (Universitas Faletehan, 2024)
Chronic Energy Deficiency (CED) can occur in pregnant women with poor nutrition. A preventive effort to address this issue is the administration of Fe3 tablets. The performance of healthcare workers in distributing Fe3 tablets is partially determined by teamwork. This study aimed to analyze the relationship between the five dimensions of teamwork and the performance of Fe3 tablet administration at community health centers in Jombang Regency. This research was observational, involving 34 respondents representing each community health center in Jombang Regency. The data analysis was conducted using cross-tabulation and cross-sectional study. The results indicated that teamwork factor in the aspect of team leadership was almost evenly balanced between good and poor. The teamwork factors in the aspect of team orientation and mutual performance monitoring were good in most community health centers. The teamwork factor in the backup behavior dimension was almost equally divided between good and adequate. The teamwork factor in the adaptability dimension was good in most community health centers. The performance results of community health centers in 2018 regarding the administration of Fe3 tablets to pregnant women fell into the adequate category. The teamwork factors in the dimensions of team orientation, team leadership, mutual performance monitoring, and adaptability were related to performance outcomes. However, the backup behavior dimension had no relationship with performance outcomes.